2010
DOI: 10.1007/s10029-009-0623-x
|View full text |Cite
|
Sign up to set email alerts
|

Composite mesh migration into the sigmoid colon following ventral hernia repair

Abstract: Ventral hernia repair is frequently performed with one of a number of mesh products, usually with good results. The current emphasis on laparoscopic repair has resulted in multiple composite mesh products for use in the peritoneal cavity. The addition of a second layer of more inert material to the mesh is intended to prevent adhesions with the underlying viscera, and multiple studies demonstrate effectiveness in doing this. Despite this, occasional complications may still present. We present the case of a 65-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 4 publications
0
20
0
1
Order By: Relevance
“…However, the best Intra-operative view: the Mersilene plate was in contact with the intestinal loops, which are home to two holes pipelined by two probes treatment remains prevention by avoiding placing the synthetic material directly over the viscera [1][2][3][4][5]. Furthermore, composite meshes are available and may decrease the frequency of this complication, but they do not completely protect from late-onset fistulae [7].…”
Section: Discussionmentioning
confidence: 98%
“…However, the best Intra-operative view: the Mersilene plate was in contact with the intestinal loops, which are home to two holes pipelined by two probes treatment remains prevention by avoiding placing the synthetic material directly over the viscera [1][2][3][4][5]. Furthermore, composite meshes are available and may decrease the frequency of this complication, but they do not completely protect from late-onset fistulae [7].…”
Section: Discussionmentioning
confidence: 98%
“…In the other case, that is, a male patient who underwent ventral hernia repair, an enterocutaneous fistula was discovered intraoperatively and diagnosed by the surgeon as a sigmoidal mass. When the surgeon resected the mass, he noticed mesh migration to the sigmoid colon [ 21 ]. Also, Millas et al reported a case of a composite mesh migration.…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde, kesi fıtığının onarımından sonra bağırsak içine mesh göçü olgularının sayısı, bizim olgumuzla birlikte 3 adettir. 6,7 Kasık fıtığının mesh ile onarımı sonrasında barsak içine mesh Genel Cerrahi 1422 migrasyonu olguları da bildirilmiştir. 8 Bildirilen tüm olgularda neden olarak özellikle meshin yerleştirilme şekli ile tespitinde kullanılan sütür materyali ve tekniği sorgulanmıştır.…”
Section: Discussionunclassified